Returning to the Classroom: A Narrative Inquiry into the Challenges and Coping Strategies of an EFL Teacher Resuming After Hiatus - Romadhon, M.Galuh Elga; Mustofa, Mutmainnah; Elfiyanto, Sonny; Rifyani, Andri Jamaul (Universitas Hamzanwadi, 2023)
This qualitative study employs narrative inquiry to investigate the challenges and coping strategies of T1, an EFL teacher at an Islamic private elementary school, returning to teaching after a hiatus. Through unstructured interviews, it examines the changes in T1's teaching approach before and after the break, uncovering unique challenges and adaptive strategies. The research reveals T1's struggle with readjustment, curriculum changes, and lesson planning without standard textbooks. To navigate these challenges, T1 utilized familial support, embraced technological resources for professional growth, and innovatively combined traditional and modern teaching methods. These findings emphasize the importance of continuous professional development, adaptability, and robust support systems in enhancing the reintegration process for EFL teachers. The study contributes valuable insights into the EFL field, highlighting the need for resources and strategies to support teachers like T1 in transitioning back to the classroom. This research not only sheds light on the specific challenges faced by returning EFL teachers but also underscores the critical role of support systems and professional development in maintaining high-quality EFL education.